A routine method for the semi-quantitative determination of porous carbonaceous material in wastewater matrices - Margreiter, C.; Hofmann, A.; Wagner, A. O. (Frontiers in Environmental Engineering, 2026)
The EU directive 2024/1990/EU mandates a fourth treatment stage for micropollutant removal in wastewater treatment plants (WWTPs). Porous carbonaceous materials (PCMs) such as powdered activated carbon (PAC) and biochar are effective but require monitoring. This study presents a semi-quantitative, low-cost method for PCM determination in wastewater matrices using total carbon (TC) analysis. Calibration curves were established for activated sludge (AS), excess sludge (ES) and anaerobic digestion sludge (ADS) matrices, yielding high linearity (R2 > 0.99). Limits of detection (LOD) and quantification (LOQ) ranged from 0.10 to 0.25 gPCM/gDM. Recovery rates exceeded 95% for AS and ES matrices, with relative standard deviations below 5%, demonstrating excellent precision. Comparison with chemical oxygen demand (COD)-based estimates showed strong correlation, validating the approach. The method enables routine PCM monitoring in WWTPs lacking sophisticated analytical equipment, supporting regulatory compliance and process optimization. While native organic carbon cannot be excluded and the relatively high LOD reduces sensitivity, the method still delivers robust semi-quantitative estimates for basic routine PCM monitoring.